Foreign trade structure, opening degree and economic growth in Western China - Nan Li; Lipeng Sun; Xiao Luo; Rong Kang; Mingde Jia (Economies, 2019)
This paper presents an interactive study on the relationship between the foreign trade structure, opening degree and economic growth of the provinces in western China (except Tibet). It shows that the export of primary products and labor-intensive products has a positive impact on the external development of the western region, while the export of capital and technology-intensive products has a smaller inhibitory effect on it. At the same time, the system GMM model shows that the opening degree of the western region has a positive effect on economic growth. After including the foreign trade structure interaction item, this result has not changed, and on the basis of opening up to the outside world, the export of labor-intensive products and capital-intensive products plays a significant role in promoting economic development. Therefore, this paper holds that the western region should optimize its foreign trade structure, continue to promote the construction of foreign trade demonstration, and give priority to the development of local characteristic industries to promote economic growth.
Keywords: 330; foreign trade; opening degree; economic growth